Chiny jako nowy czynnik w globalnym układzie sił ekonomiczno-politycznych - Dobroczyński, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
For a long time, practically since the beginning of 19. Century till 1977 (Deng's "revolution"), China was a stagnating, economically underdeveloped country, largely subordinated to foreign influences or even military invasions. However, due to a very unusual combination of historical traditions, autocratic political power and predominantly market economy, in the recent twenty few years China has been transformed into modern, the most dynamic economy in the world scale. Co-operating systematically with foreign partners in all possible areas, such as trade, direct investments, credits, services. And in politics, culture, science, sports. Insisting on proper, correct relations with all major powers - including the United States and Japan. Entering into integrational relations with the neighbouring countries of ASEAN. And, though very slowly, democratizing internal political or social structures as well. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 102-112